(untitled) (Russian Medical and Social Journal, 2019)
To the 75th anniversary of appellation the name of The Red Army Main Military Hospital to The 1-st Moscow Communist Military Hospital the history of Moscow hospital opening in 1706-1707 was briefly described. Scientific and medical breakthroughs and increasing role of the hospital as a medical, educational and scientific institution for a Red Army military medical service in 1917-1945 was shown in more details. It also included intensive complicated hospital operation period during The Great Patriotic War 1941-1945 (as a part of World War II).